Eski Türk Ticaret Kanunu ile yeni Türk Ticaret Kanunu'nda anonim ortaklıkların genel kurulu - Boran, Tuğba (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Özel Hukuk Anabilim Dalı / Özel Hukuk Bilim Dalı, 2011)
Genel kurul, anonim ortaklığın vazgeçilmez zorunlu bir organıdır. Anonim ortaklık, genel kurul tarafından alınan kararlar ile yönetilir. Ortaklığın iradesi genel kurulda oluşur. Bu çalışmamızda genel kurulun oluşumunu ve işleyişini, TTK hükümleri ile Yeni TTK hükümleri ışığında inceledik. Anonim ortaklık genel kurulu, TTK m. 360 vd. düzenlenen, nasıl toplanacağı, toplantı zamanı, oy ve müzakereler ile karar alınması aşamalarını içeren zorunlu bir organdır. Tezimizin birinci bölümünde, anonim ortaklık genel kurulunun tanımını, özelliklerini, yetkilerini inceledik. Ayrıca genel kurulu sınıflandırarak alt başlıklar içinde diğer genel kurul toplantılarına değindik. İkinci bölümde, genel kurul toplantısına katılacakları tespit ettikten sonra, toplantıya davetin yapılmasını, komiserin istenmesini ve hazirun cetvelini ele aldık. Ayrıca, genel kurul toplantılarını, bu toplantıların işleyişini ele alarak komiserin görevlerine değindik. Ardından genel kurul toplantı tutanağını ele aldık. Son bölümde genel kurul toplantısında oylamadan bahsederek genel kurulda kararın oluşumuna ve etkilerine değindik.

General shareholder?s meeting is an indispensable and compulsory organ of the joint stock corporation. Joint stock corporation is managed by the decisions made in the general shareholder?s meeting. The decree of the corporation is formed at the general shareholder?s meeting. In this study, we have inspected the formation and the process of the general shareholder?s meeting, in the light of TTK (Turkish Commerce Law) arbitraments and the new TTK (Turkish Commerce Law) arbitraments. Joint stock corporation general shareholder?s meeting is a compulsory organ which is arranged by TTK (Turkish Commerce Law) clause 360 and continuing , and contains how to hold a meeting,the time of the meeting, the stages of decision-making by votes and negotiations. In the first part of the thesis, we have inspected the definition, characteristics and powers of the joint stock corporation general shareholder?s meeting. Furthermore, by classifying general shareholder?s meeting , we have dealt with other board meetings throughout subtitles. In the second part , having determined the attendants of the general shareholder?s meeting, we have discussed the intivitation to the meeting, asking for the officer and the attendant list.Besides, we have dealt with board meetings and the duties of the officer by handling the process of these meetings. Then we discussed board meeting records.In the last part, while we are referring to voting in board meeting, we have dealt with the formation of the decision at the general shareholder?s meeting and its effects.
In the frame of the Turkish Commerce Law and new Turkish Commerce Law general shareholder's meeting in the join stock corperations
Keywords: Hukuk; Anonim ortaklıklar; Genel kurul; Genel kurul kararları; Ticaret Kanunu; Türk Ticaret Kanunu; Law; Incorporated companies; General assembly; General assembly resdutions; Commercial Code; Turkish Commercial Code